Analisa Perubahan Cuaca Di Pulau Sumatera Akibat Kebakaran Hutan Dengan Data Water Vapor Dari Citra Satelit Terra Modis - Oktalia Triananda Lovita; Mokhamad Nur Cahyadi; Muhammad Taufik (Jurnal Inotera, 2017)
Forest fires in Sumatra lead to a very extreme climate changes around the earth, so there would still be a difficult job for atmosphere researchers. This research was conducted to know the weather conditions by determining the condition of Water Vapor (WV) on the island of Sumatra. Monitoring the condition of WV can be done by using remote sensing techniques, by processing the image satellite data namely Terra Modis (Moderate Resolution Imaging Spectroradiometer). Data calculation condition WV, as one of the parameters of dynamic atmosphere. The data comes from Terra Modis satellite image, the data on Canal 2, 5, 17, 18 and 19 with a wavelength range; 0,865μm, 1.24 μm, 0.905 μm, 0.936 μm and 0,940 μm. From these results obtained from the average value of Water Vapor before and after fires in 2012. Water Vapor taken from TERRA MODIS satellite imagery (y) with a correction factor of 0.9865. Although the correlation (r) between Water Vapor from MODIS data is high, it can be seen that between Water Vapor in 2012 ranged between 3-8 cm. 82%, however only about 68% of Water Vapor MODIS diversity that can be presented by the equation model to approach the actual value of Water Vapor. With these data will greatly affect the weather cycle in Indonesia.